The Role of Innovation in Sustainable Regional Development - Štefenberga, Dace; Sloka, Biruta (My University, 2020)
Innovation–it is a term that we use for decades, but true meaning of this term changes also for decades, according to dynamic environment we are living in. There is now beginning of the4thindustrial revolution and what has been said in World Economic forum, issues are not about technologies anymore, they are about society. Innovation and entrepreneurship in regions is one of essential tools, in added value creation in economics and in development in national level. It is very important to encourage creativity, new ways of thinking and continuous process of learning of individuals. Aim of the current paper is to investigate development of application of innovations evaluated internationally for the country by GCI and reflect the entrepreneur’s opinions for innovation applications aspects. Research methods applied: scientific publications and previous conducted research results analysis, analysis of development of reflection innovation aspect in GCI, analysis of strategic planning documents and guidelines of EU and Latvia and survey of inhabitants of local community survey of entrepreneurs of Kurzeme region in Latvia on their opinion about participation in the processes to make changes in development of region and local community. There are some different approaches how to measure competitiveness of state economy and competitiveness in regional level. Statistical data shows situation from point of view in national level, Regional level and local community level have to be researched detailed, and every situation, which can make impact on level above, have to be taken into account. Main results were related with issue, that tenants of region at very low level evaluate impact of state as institution and management system in national level, better evaluation of local government institutions, but at the same time there is lack of desire to participate actively in processes of local community to encourage changes in regional level.
Keywords: Global Competitiveness Index; innovation; regional development; Research Subject Categories::SOCIAL SCIENCES::Business and economics